Trend analysis of Pahang river using non-parametric analysis: Mann kendall’s trend test [Analisis corak sungai Pahang menggunakan kaedah bukan parametrik: Ujian Mann Kendall] - Mohd Khairul Amri, Kamarudin; Nur Hishaam, Sulaiman; Ahmad Dasuki, Mustafa (Malaysian Society of Analytical Sciences, 2015)
Flood is common in Pahang especially during northeast monsoon season from November to February. Three river cross station: Lubuk Paku, Sg. Yap and Temerloh were selected as area of this study. The stream flow and water level data were gathered from DID record. Data set for this study were analysed by using non-parametric analysis, Mann-Kendall Trend Test. The results that obtained from stream flow and water level analysis indicate that there are positively significant trend for Lubuk Paku (0.001) and Sg. Yap (< 0.05. Temerloh (0.178) data from 1963-2011 recorded no trend for stream flow parameter but negative trend for water level parameter. Hydrological pattern and trend are extremely affected by outside factors such as north east monsoon season that occurred in South China Sea and affected Pahang during November to March. There are other factors such as development and management of the areas which can be considered as factors affected the data and results. Hydrological Pattern is important to indicate the river trend such as stream flow and water level. It can be used as flood mitigation by local authorities.